Phylogeny, biogeography, and character evolution of Anaphalis (Gnaphalieae, Asteraceae) - Xu, Xue-Min; Xu, He; Yang, Zheng; Wei, Zhen; Gu, Jun-Yu; Liu, Dan-Hui; Liu, Quan-Ru; Zhu, Shi-Xin (Frontiers in Plant Science, 2024)
The HAP clade, mainly including Helichrysum Mill, Anaphalis DC., and Pseudognaphalium Kirp., is a major component of tribe Gnaphalieae (Asteraceae). In this clade, Anaphalis represents the largest genus of Asian Gnaphalieae. The intergeneric relationships among Anaphalis and its related genera and the infrageneric taxonomy of this genus are complex and remain controversial. However, there are few studies that have focused on these issues. Herein, based on the current most comprehensive sampling of the HAP clade, especially Anaphalis, we conducted phylogenetic analyses using chloroplast (cp) genome and nuclear ribosomal DNA (nrDNA) to evaluate the relationships within HAP clade, test the monophyly of Anaphalis, and examine the infrageneric taxonomy of this genus. Meanwhile, the morphological characters were verified to determine the circumscription and infrageneric taxonomy system of Anaphalis. Additionally, the biogeographical history, diversification processes, and evolution of crucial morphological characters were estimated and inferred. Our phylogenetic analyses suggested that Anaphalis is polyphyletic because it nested with Helichrysum and Pseudognaphalium. Two and four main clades of Anaphalis were identified in cp genome and nrDNA trees, respectively. Compared with nrDNA trees, the cp genome trees were more effective for phylogenetic resolution. After comprehensively analyzing morphological and phylogenetic evidence, it was concluded that the achene surface ornamentation and leaf base showed less homoplasy and supported the two Anaphalis lineages that were inferred from cp genome. Our biogeographical analyses based on cp genome indicated that HAP clade underwent rapid diversification from late Miocene to Pliocene. The two Anaphalis lineages appeared to have originated in Africa, then spread to Western and Southern Asia, and subsequently moved into Southwestern China forming a diversity center. The dispersal patterns of the two Anaphalis lineages were different. One dispersed around the world, except in Africa and South America. The other one dispersed to Eastern and Southeastern Asia from the ancestral origin region.